The impact of the use of mental perception in the annual physical preparation program to improve some of the physical and skill capabilities of volleyball players - lebchiri ahmed, (sports creativity, 2025)
This study amisto determine the effect of the use of mental perception in the physical preparation to improve skills development programs in volleyball, through the application of mental visualization program on the experimental group the general and specific physical. the study concluded thatthe use of mental perception at this stage improves the skills development the players according to differences in the statistical treatment, and that the most important results obtained it to emphasize the importance of using these programs to develop the skills capacity of the volleyball playe